DTS, or et monnaies : Troisieme expose sur les changements intervenus dans le domaine juridique. (Pamphlet Series, 1980)
This paper presents the fourth survey of certain changes in international and national monetary law and practice in relation to special drawing rights (SDRs), currencies, and gold. SDRs have characteristics that enable them to function as a supplement to existing reserve assets in the sense that they can be used as a form of international liquidity by members of the IMF participating in the SDR Department. The IMF has taken decisions to expand the uses of the SDR. Whether or not any of the newly authorized operations take place, the decisions authorizing them must be taken into account in any legal analysis of the character of the SDR.